Efficacy of topical 1% pimecrolimus cream in the treatment of atopic dermatitis - Sultana, A; Begum, A; Bhuiyan, MMSI; Zakaria, ASM; Rabin, F; Fakir, AY; Ahmed, S; Ahmed, S (Journal of Dhaka Medical College, 2012)
DOI: http://dx.doi.org/10.3329/jdmc.v20i2.10548 J. Dhaka Med. Coll. 2011; 20(2): 188-192